2021
DOI: 10.34069/ai/2021.47.11.7
|View full text |Cite
|
Sign up to set email alerts
|

The change in the concept of virtue during the COVID-19 pandemic

Abstract: The purpose of the article is to cover the change in the concept of virtue during the COVID-19 pandemic, show its connection with human values and ethics. Virtue is the highest spiritual quality of a person. The main virtues include wisdom, courage, justice, moderation, responsiveness, loyalty, modesty, generosity and many others that affect all aspects of human life. Despite the recognized value of virtue as a system of moral guidelines, its concept is fraught with disputes about whether it is really generall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…In particular, it has been found that the Ukrainian military do not tend to experience excessive anxiety in anticipation of going to the front line and are characterized by a low or unexpressed degree of frustration, indicating their ability to set and achieve goals and be satisfied with the outcomes of their actions. It is possible to assume that this state is ensured by their positive response to stressful events, which occurs in extreme or crisis situations, a result consistent with the findings of the study by Rybinska et al (2021). In particular, the need to participate in hostilities can increase the emotional stability of Ukrainian military personnel, strengthen or stimulate their courage and help shape their common goals and ideology that dull the feeling of anxiety.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In particular, it has been found that the Ukrainian military do not tend to experience excessive anxiety in anticipation of going to the front line and are characterized by a low or unexpressed degree of frustration, indicating their ability to set and achieve goals and be satisfied with the outcomes of their actions. It is possible to assume that this state is ensured by their positive response to stressful events, which occurs in extreme or crisis situations, a result consistent with the findings of the study by Rybinska et al (2021). In particular, the need to participate in hostilities can increase the emotional stability of Ukrainian military personnel, strengthen or stimulate their courage and help shape their common goals and ideology that dull the feeling of anxiety.…”
Section: Discussionsupporting
confidence: 81%
“…In other words, when evaluating fear as an element of a person's psycho-emotional state under conditions of stressful events, it is also necessary to take into account additional social factors. At the same time, Rybinska et al (2021), in their article, argue that stressful situations can also have a positive effect on a person's psychological or emotional resilience. In particular, their study of the impact of the coronavirus pandemic on society on a global scale has revealed that the stress experienced during the pandemic has increased the manifestations of many virtues.…”
Section: Psycho-emotional Reactions To Stressful Eventsmentioning
confidence: 99%
“…The most significant shift in the concept of virtue dur-ing the pandemic was the rethinking and increased awareness of the importance of virtues such as solidarity and moral responsibility, as well as aspects of relationships with people such as kindness, compassion, and empathy. 4) The COVID-19 outbreak has revealed that both governments and individuals must take moral responsibility to overcome the pandemic. 5) What are the essential roles of virtues in the fight against chronic diseases and in improving public health in general?…”
Section: To the Editormentioning
confidence: 99%